Aeromonas salmonicida activates rainbow trout IgM(+) B cells signalling through Toll like receptors - Soleto, Irene (Sci Rep, 2020)
As B cells are singularly equipped with a B cell receptor (BCR) and a range of innate receptors, they are able to integrate both antigen-specific and innate signals, with the latter being essential to reach an adequate level of activation. Whether teleost B cells sense pathogens through innate mechanisms has not yet been explored, despite the fact that fish B cells display a wider array of innate receptors than many mammalian B cell subsets. Hence, in the current study, we have investigated the effects of inactivated Aeromonas salmonicida, a Gram negative rainbow trout pathogen, on trout splenic IgM(+) B cells in vitro in the presence or absence of different inhibitors of Toll-like receptor (TLR) signalling, to establish to what degree innate signals are contributing to the activation of B cells in teleosts. Our results demonstrate that most of the effects that A. salmonicida exerts on trout IgM(+) B cells are significantly blocked in the presence of inhibitors of MyD88 and TRIF, important nodes in TLR signal pathways. Thus, the data presented demonstrates that, also in teleost, TLR signalling is essential for the activation of IgM(+) B cells. These results will be useful for the future optimization of novel vaccines and adjuvants.